Promoción y prevención en salud oral asistida virtualmente dirigida a niños de primer y segundo grado y sus representantes legales del colegio Simón Bolívar (2021)
Objectives. Develop activities in promotion and prevention in oral health assisted virtually directed to children and their legal representatives first and second grade of the Simón Bolívar school. Materials and methods. A descriptive/observational design was applied in which 137 legal representatives and 143 first and second-grade children of the Simon Bolivar school, Hernando Acevedo and San Martin campus, participated in the first survey to evaluate the level of knowledge in oral health and oral hygiene habits, before and after the pedagogical strategies carried out. Posterior to the first survey, pedagogical approaches in oral health and habits were developed to promote oral health promotion and prevention, assisted virtually by talks directed to legal representatives and modern theater in children. Results. It was observed that the representatives had good knowledge about oral health habits before the intervention. After it, the results showed a significant improvement. On the other hand, Children presented a notable lack of knowledge about oral health habits before the intervention. After this, the level of knowledge increased auspiciously; it is of great importance, the educational talks about oral health habits since it helps us improve our healthy lifestyle